The German vocational education and training system: Its institutional configuration, strengths, and challenges - Heike Solga; Paula Protsch; Christian Ebner; Christian Brzinsky-Fay (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2014)
Germany is widely known for its high-quality vocational education and training (VET) system. The two key features of that system are (a) firm-based training programs accompanied by a schoolbased component (of one to two days per week), in which apprentices acquire upper secondary general education in core subjects (like math and German) and theoretical knowledge in their training occupation. This duality of practical and theoretical knowledge acquired at the workplace and at vocational schools is (b) accompanied by the private-public duality in the governance structure (i.e., public governance of the vocational schools, provide governance of the firm-based training). In the recent recession, this so-called dual system has received much international attention, for instance in the US, UK, or Spain. Whereas youth unemployment has increased enormously in the last years in many (European) countries, this has not been the case in Germany. From the outside, therefore, it may look as if Germany's low youth unemployment rate is to be credited to the dual system. That observation, however, is only partly correct, as we will discuss in this paper. The aim of this paper is to provide information on the German VET system, enabling international readers to better understand its institutional setting, its strengths and appeal, but also its challenges and weaknesses. Therefore, the paper is structured as follows. We will start with the institutional configuration of the German VET system (Section 2), describing its institutional prerequisites and its different sectors. As we will see, there is more to Germany's VET system than the well-known dual system. We will proceed by presenting some historical developments, necessary to understand the longevity of Germany's VET system and the ways in which it has dealt with the challenges of transitioning towards a "knowledge-based" society (Section 3). In Section 4, we will discuss both the potential and the problems of the apprenticeship system with regard to including low-achieving or disabled youth. Afterwards, we will briefly compare Germany to the dual systems of Austria, Denmark and Switzerland (Section 5). This comparison will reveal that the framework of a dual system allows for a variety of configurations - an information that might be of special interest to international readers who want to better understand Germany's "exceptionalism" regarding the divide between vocational and general higher education. We will conclude the paper with some findings regarding the importance of the German VET system in terms of labor market entry (Section 6) and some lessons that can be learnt from the insights presented in the paper.
Keywords: 330